THE INFLUENCE OF PHYTOHORMONES ON SEED DORMANCY AND GERMINATION IN DESERT PLANTS: A COMPREHENSIVE REVIEW - Dr. Jyoti Agrawal; Dr. Archana Tiwari; Dr. Touseef Begum; Dr. M Vijaya Simha (The Bioscan, 2025)
The fundamental processes of seed dormancy and germination enable plants to survive, procreate, and persist in desert ecosystems characterised by erratic rainfall, extreme temperatures, and a scarcity of resources. Here, seeds go through a number of hormonal and physiological changes that prevent them from germinating unless the right circumstances are met, which is extremely uncommon. Gibberellins (GA) and abscisic acid (ABA) are the two primary antagonistic hormones that control the dormancy–germination switch; one promotes radicle protrusion and seedling growth, while the other supports quiescence and stress tolerance. Furthermore, in addition to their interactions, auxins, cytokinins, ethylene, brassinosteroids, and jasmonates also influence hormone sensitivity, reserve mobilisation, and mechanical barrier deterioration. Reactive oxygen species (ROS) and nitric oxide (NO), two very small molecules, can function as environmental cues that trigger hormonal cascades. Desert plants are so well-equipped that they can alter the way their hormones are metabolised while still managing to keep their seeds in the subterranean soil, allow them to cycle through dormancy, and allow them to germinate shortly after the rain, albeit briefly. Recent molecular mechanisms have shown that transcription factors, hormone carrier proteins, and catabolic enzymes are involved in the precise regulation of these processes, and ecological studies have identified dormancy heterogeneity and bet-hedging as two strategies for plant survival in those conditions. We should welcome and use this type of information for climate change adaptation, dryland agriculture, and restoration ecology. This review’s integration of genetics, ecology, and hormone regulation is a potent tool for advancing the field of seed biology and, in turn, for enhancing the management of desert ecosystems through the application of creative techniques.